Association between blood lead and periodontitis among American adults: a cross-sectional study of the national health and nutrition examination survey - Liu, Yang; Wu, Yuchuan; Shi, Xiaolu; Tian, Ye; Zhai, Shaobo; Yang, Zheng; Chu, Shunli (Frontiers in Pharmacology, 2024)
Background: Lead is persistent in the environment as a toxic substance and accumulates in the human body. Lead exposure has far-reaching harmful effects on all human systems and is widely recognized as a health and public health concern. Lead exposure poses a significant risk to oral health, as it destroys salivary glands and alveolar bone. It also induces oxidative stress which results in an immune response. Lead exposure appears to adversely affect periodontal tissues. Currently, the available evidence on the relationship between blood lead and periodontitis is insufficient and further research is necessary.Objective: In this study, the objectives were to clarify the association between blood lead and periodontitis, as well as to explore potential dose-response relationships between blood lead exposure and periodontitis, as well as to determine appropriate thresholds for the effects of blood lead on periodontitis. Methods: We conducted a cross-sectional study involving 8550 participants with American adults aged 30 or older. blood Lead, periodontitis, age, sex, race, heart rate, education level, poverty index, marital status, body mass index, smoking status, alcohol drinking status, hypertension, diabetes and stroke. were collected from participants. logistic regression, smooth curve fittingwere utilized to substantiate the research objectives. Results: There were a total of 8550 participants of which 52.2% (4467 /8550) had moderate/severe periodontitis. Compared with Q1 (0.15-0.93 ug/L), where blood lead levels were lower, the OR values for adjusted blood lead and periodontitis in Q2 (0.93-1.60 ug/L) and Q3 (1. 60-61.29ug/L) were 1.18 (95% CI: 1.12-1.25, P < 0.001) and 1.43 (95% CI: 1.34- 1.52, P < 0.001).The association between blood lead levels and periodontitis exhibited a curve (non-linear, p < 0.001), with an inflection point of roughly 2.700ug/L. The OR values for moderate/severe periodontitis in participants with blood lead levels <2.700ug/L was 1.318 (95% CI: 1.193-1.457, p < 0.001). Conclusions : Blood lead levels are positively associated with periodontitis. Blood lead levels increased by five units and were associated with an increase in moderate and severe periodontitis risk by 36%. There is a curvilinear relationship between blood lead and periodontitis with a threshold effect and an inflection point of approximately 2.7 ug/L.